Proteases Regulate Cancer Stem Cell Properties and Remodel Their Microenvironment. (December 2021) - Habič, Anamarija; Novak, Metka; Majc, Bernarda; Lah Turnšek, Tamara; Breznik, Barbara
Proteolytic activity is perturbed in tumors and their microenvironment, and proteases also affect cancer stem cells (CSCs). CSCs are the therapy-resistant subpopulation of cancer cells with tumor-initiating capacity that reside in specialized tumor microenvironment niches. In this review, we briefly summarize the significance of proteases in regulating CSC activities with a focus on brain tumor glioblastoma. A plethora of proteases and their inhibitors participate in CSC invasiveness and affect intercellular interactions, enhancing CSC immune, irradiation, and chemotherapy resilience. Apart from their role in degrading the extracellular matrix enabling CSC migration in and out of their niches, we review the ability of proteases to modulate CSC properties, which prevents their elimination. When designing protease-oriented therapies, the multifaceted roles of proteases should be thoroughly investigated.